QUADRUPLE HELIX IN POLICY DESIGN: RETHINKING INDUSTRIAL REVITALIZATION IN TRANSITIONAL ECONOMIES - Anton Andriienko (Three Seas Economic Journal, 2025)
This article comprehensively examines the relevance and operationalization of the Quadruple Helix (QH) model as a transformative framework for designing robust industrial policy within transitional economies. The study focuses on integrating academia, industry, government, and civil society as co-equal stakeholders in innovation and economic governance. This is particularly pertinent given the systemic challenges inherent in post-socialist and post-crisis contexts, often characterized by profound institutional fragility, civic disengagement, and significant policy fragmentation. Traditional, top-down approaches to industrial revitalization have proven insufficient and unsustainable in such complex environments. The QH model offers a powerful normative and functional framework, offering a foundation for inclusive, democratic, and resilient policy co-creation processes that can genuinely address these underlying systemic weaknesses. The study employs a rigorous mixed-method qualitative approach. It begins with a systematic literature review of Quadruple Helix theory, exploring its conceptual evolution, theoretical underpinnings, and practical applications, including a comparative analysis of Triple versus Quadruple Helix governance structures. Building on this, the research constructs a novel conceptual framework centered on four critical governance functions: knowledge co-creation, institutional bridging, participatory legitimacy, and adaptive governance. This framework is subsequently tested and illustrated through three documented case studies: from Lithuania, Finland, and EU Interreg regions. These cases, drawing on diverse empirical evidence, provide rich insights into how QH mechanisms operate and translate into tangible policy outcomes across varied environments. The overarching goal of this article is to develop a practical, theoretically grounded, and empirically informed model for QH-based industrial policy specifically tailored for transitional settings. It seeks to demonstrate that genuine stakeholder co-creation, when appropriately institutionalized through clear legal mandates, robust intermediary platforms, and feedback-driven iterative governance processes, can effectively address deep-seated policy inertia, enhance public trust, and significantly bolster policy legitimacy. The findings clearly demonstrate that QH-informed approaches foster enhanced cross-sectoral coordination and resource mobilization, enabling critical place-based adaptability and promoting sustained, meaningful civic engagement. However, the research also highlights persistent challenges, including civic capacity gaps, the risk of symbolic participation, and resource limitations, particularly where enabling legal and institutional infrastructures are underdeveloped. In conclusion, the article firmly asserts that the Quadruple Helix model holds significant potential as a transformative governance logic for industrial revitalization. When thoughtfully adapted to the unique realities of transitional economies, it provides a robust foundation for policy design that is both deeply participatory and finely context-sensitive. The model moves beyond mere rhetorical inclusion of stakeholders, emphasizing the imperative need for systemic structures and processes that actively support long-term, democratic, and inclusive innovation. Policymakers are encouraged to embed QH principles through formal frameworks, dedicated funding, and iterative co-design practices to truly realize inclusive and sustainable industrial development that benefits all societal actors.